Unpacking the black box: How to promote citizen engagement through government social media during the COVID-19 crisis - Chen, Qiang; Min, Chen; Zhang, Wei; Wang, Ge; Ma, Xiaoyue; Evans, Richard (Computers in human behavior, 2020)
During times of public crises, governments must act swiftly to communicate crisis information effectively and efficiently to members of the public; failure to do so will inevitably lead citizens to become fearful, uncertain and anxious in the prevailing conditions. This pioneering study systematically investigates how Chinese central government agencies used social media to promote citizen engagement during the COVID-19 crisis. Using data scraped from ‘Healthy China’, an official Sina Weibo account of the National Health Commission of China, we examine how citizen engagement relates to a series of theoretically relevant factors, including media richness, dialogic loop, content type and emotional valence. Results show that media richness negatively predicts citizen engagement through government social media, but dialogic loop facilitates engagement. Information relating to the latest news about the crisis and the government's handling of the event positively affects citizen engagement through government social media. Importantly, all relationships were contingent upon the emotional valence of each Weibo post. •This study investigates how to promote citizen engagement through government social media during the COVID-19 crisis.•Media richness negatively predicts citizen engagement, but dialogic loop facilitates engagement.•Information relating to the latest news and the government's handling positively affects citizen engagement.•All relationships were contingent upon the emotional valence of each Weibo post.